The Possible Uses of Foldscopes as a Form of Frugal Science in the Biology Classroom As Well As in Out-of-School Science Activities - Jannie Pretorius; Josef de Beer; Cherine Jackson (Research in Social Sciences and Technology, 2023)
This article explores the possibilities of a cheap one-dollar microscope, the Foldscope, for enhancing out-of-school science education. Developed by Manu Prakash and Jim Cybulski from Stanford University, these origami-type paper microscopes make it possible to provide all students with their own microscopes, due to the low cost. This provides students the opportunity to engage in science outside of the classroom, as amateur sleuths engaged in environmental inquiries, e.g., determining the levels of pollution of local water resources. In this article the authors share two sets of research data: an activity where school students engaged in authentic problem-based learning using the Foldscopes, as well as student teachers’ experiences of engaging with Foldscope microscopes. The outcomes of the first research project indicate that affective outcomes and cognitive gains were achieved. Responses in the second research project included five categories: preparation and presentation; potential of the Foldscope; use of slideshow; energy/complements; and limitations. The conclusion reached was that Foldscopes hold possibilities for enhancing STS (science-technology-society) approaches inside and outside the classroom. One recommendation is that such frugal-science approaches are emphasized more in both pre-and in-service teacher education.